Retention of bar clip attachment for mandibular implant overdenture - Hossam I. Nassar; Medhat Sameh Abdelaziz (BMC, 2022)
Abstract Objectives The aim of the present study was to evaluate the retention and loss of retention after fatigue testing at different time intervals between two types of bar clip materials (digitally designed PEEK bar clip and regular Nylon bar clip). Materials and methods An epoxy model was constructed for a completely edentulous mandible. Two implants were placed according to prosthetically driven implant placement by a computer-guided surgical stent. Bar clips were digitally designed, 3D printed, and pressed into Poly Ether Ether Ketone (PEEK). Pick up of PEEK and nylon clips was performed on the dentures fitting surface using self-cured acrylic resin. Each study group was subjected to an insertion and removal fatigue test simulating 3 years of patient usage. Retention values were recorded using the universal testing machine at initial retention and after 1, 2, and 3 years of simulated usage. For proper sample sizing, 24 models and dentures (12 for each group) were used. An independent sample t-test and repeated measures analysis of variance were used to compare the data. Results There were statistically significant differences in retention between the PEEK and nylon bar clips at the beginning of the experiment (p = 0.000*). But after 3 years of simulated use, there was no significant difference in retention between the test groups (p = 0.055, NS). After 3 years of simulated use, the retention of PEEK clips decreased by − 58.66% recording 17.37 ± 1.07 N, while the retention of nylon clip increased by + 2.99% recording 16.56 ± 0.88 N. Conclusion The digitally designed PEEK clip showed comparable retention results to the nylon clip after 3 years of simulated use. Clinical relevance Maintenance of bar attachment with PEEK clip offers a clinical solution after the wear of normal plastic clips, which is a cheap solution that is easily fabricated and picked up into the denture. Digital fabricated PEEK bar retentive inserts can be used in cases of bar attachment wear.